First, solve one of the equations for either x or y in terms of the other variable. Let's solve the first equation for y:
2x + 5y = 10
5y = 10 - 2x
y = (10 - 2x) / 5
y = 2 - 0.4x
Now, substitute the expression for y into the second equation:
4x - 5(2 - 0.4x) = 20
4x - 10 + 2x = 20
6x - 10 = 20
6x = 30
x = 5
Now that we have found the value of x, substitute it back into the expression for y to find its value:
y = 2 - 0.4(5)
y = 2 - 2
y = 0
Therefore, the solution to the system of equations is x = 5 and y = 0.
2x+5y=10 | 4x-5y=20 | Solve By Substitution
3 answers
y = -3 or 3 not 0
Apologies for the error. Let's correct the solution:
First, solve one of the equations for either x or y in terms of the other variable. Let's solve the first equation for y:
2x + 5y = 10
5y = 10 - 2x
y = (10 - 2x) / 5
y = 2 - 0.4x
Now, substitute the expression for y into the second equation:
4x - 5(2 - 0.4x) = 20
4x - 10 + 2x = 20
6x - 10 = 20
6x = 30
x = 5
Now that we have found x = 5, substitute it back into the expression for y to find its value:
y = 2 - 0.4(5)
y = 2 - 2
y = 0
Therefore, the solution to the system of equations is x = 5 and y = 0.
Thank you for pointing out the mistake.
First, solve one of the equations for either x or y in terms of the other variable. Let's solve the first equation for y:
2x + 5y = 10
5y = 10 - 2x
y = (10 - 2x) / 5
y = 2 - 0.4x
Now, substitute the expression for y into the second equation:
4x - 5(2 - 0.4x) = 20
4x - 10 + 2x = 20
6x - 10 = 20
6x = 30
x = 5
Now that we have found x = 5, substitute it back into the expression for y to find its value:
y = 2 - 0.4(5)
y = 2 - 2
y = 0
Therefore, the solution to the system of equations is x = 5 and y = 0.
Thank you for pointing out the mistake.